2018
DOI: 10.3892/ol.2018.8862
|View full text |Cite
|
Sign up to set email alerts
|

miR‑205‑5p inhibits cell migration and invasion in prostatic carcinoma by targeting ZEB1

Abstract: Many studies have demonstrated that miRNAs have influence on tumorigenesis and progression of human cancers, including invasion and migration. Thus, the role of miR-205/ZEB1 axis for the migration and invasion of prostate cancer cells was explored in the present study. The miR-205-5p and zinc finger E-box binding homeobox 1 (ZEB1) mRNA expression levels were observed in prostate cancer tissues or cell lines via reverse transcription-quantitative PCR (RT-qPCR), and the protein level of ZEB1 was measured by west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…MiR-205 functions as a tumour suppressor in human cancers, such as breast cancer, prostatic carcinoma and oral squamous cell carcinoma [27][28][29]. Our study found that miR-205 suppressed the glucose uptake, migration and invasion of glioma cells.…”
Section: Discussionmentioning
confidence: 48%
“…MiR-205 functions as a tumour suppressor in human cancers, such as breast cancer, prostatic carcinoma and oral squamous cell carcinoma [27][28][29]. Our study found that miR-205 suppressed the glucose uptake, migration and invasion of glioma cells.…”
Section: Discussionmentioning
confidence: 48%
“…[64,65] Quantitative PCR analysis revealed that the selected microRNAs were reproducibly detectable at heterogeneous levels in all BCSC lines ( Figure S5A). In particular, miR-205-5p, which is well known to inhibit ZEB1 expression directly targeting its 3'UTR [66], was inversely expressed compared with ZEB1 in all BCSC lines ( Figure S2G and S5A). Throughout the chemotherapeutic stress and recovery processes, most miRNAs in question were differentially regulated ( Figure S5B,C).…”
Section: Chemotherapeutic Stress Changes Cancer-related Mirna Expressmentioning
confidence: 98%
“…7 In addition, we have identified some potential targets of miR-205-5p and their biological processes. 7,[11][12][13]47 Moreover, it has been suggested that miR-205-5p could interact indirectly via PI3K/AKT also involved in angiogenesis. In fact, it F I G U R E 5 VEGFA-mediated Vasculogenesis is regulated by miR-205-5p.…”
Section: Vegfa Mrna As a Mir-205-5p Targetmentioning
confidence: 99%
“…Statistically significant differences were set at *P < .05 is well documented that miR-205-5p acts as a tumour suppressor by regulating cell migration and proliferation. 7,[11][12][13]47 Moreover, it has been suggested that miR-205-5p could interact indirectly via PI3K/AKT also involved in angiogenesis. 13 In the present report, we have observed that VEGFA and miR-205-5p are inversely expressed ( Figure 3), inducing angiogenesis.…”
Section: Vegfa Mrna As a Mir-205-5p Targetmentioning
confidence: 99%